Teams Make You Smarter: Learning and Knowledge Transfer in Auctions and Markets by Teams and Individuals - Boris Maciejovsky; Matthias Sutter; David V. Budescu; Patrick Bernau (University of Innsbruck, Department of Public Finance, 2010)
We study the impact of team decision making on market behavior and its consequences for subsequent individual performance in the Wason selection task, the single-most studied reasoning task. We reformulated the task in terms of assets in a market context. Teams of traders learn the task's solution faster than individuals and achieve this with weaker, less specific, performance feedback. Some teams even perform better than the best individuals. The experience of team decision-making in the market also creates positive knowledge spillovers for post-market individual performance in solving new Wason tasks, implying that team experiences enhance individual problem-solving skills.
Keywords: C91; C92; 330; Wason selection task; rationality; team decision making; individual decision making; auction; Gruppenentscheidung; Wissenstransfer; Entscheidungstheorie